What are the cut-off points for vaginal manometry to differentiate women with a weak from those with a strong pelvic floor muscle contraction?: Vaginal manometry to classify a pelvic floor muscle contraction - Silva, Jordana Barbosa da; Sato, Tatiana de Oliveira; Jorge, Cristine Homsi; Armijo-Olivo, Susan; Driusso, Patricia (Universidade Federal de São Carlos, 2023)
Maximal voluntary contraction average is the best variable to identify a strong pelvic floor contraction. Abstract Background Vaginal manometry is regarded as an objective method to assess pelvic floor muscles (PFM) function and can measure several variables during contraction. Objective To determine which variables could differentiate women with/without a weak/strong PFM contraction and determine their cut-off points. Methods This is a diagnostic accuracy study performed on 156 women with a mean age of 40.4 (SD, 15.9) years. The reference test was vaginal palpation and the index test was vaginal manometry (Peritron™ manometer). Variables were pressure at rest, pressure achieved with maximal voluntary contraction (MVC), MVC average, duration, gradient, and area under the curve (AUCm). The Receiver Operating Curve (AUC/ROC) and logistic regression were used to analyze the data and obtain cut-off points. Results Excellent ability to discriminate women with a weak/strong PFM contraction was found for MVC average (cut-off: 28.93 cmH2O), MVC (cut-off: 38.61 cmH2O), and the AUCm (cut-off: 1011.93 cm²*s). The gradient variable had good discrimination ability (AUC/ROC=0.81; cut-off: 28.68 cmH2O/s). The MVC average assessed by manometry, menopausal status, and the presence of stress urinary incontinence (SUI) were associated with a weak/strong PFM contraction in the multivariate analysis; however, the most parsimonious model to discriminate weak/strong PFM contraction included only the MVC average (AUC/ROC = 0.95; sensitivity: 0.87; specificity: 0.91). Conclusion These results suggest which manometry variables are appropriate to assess and classify PFM function in females. These could be used to help physical therapists to make clinic decisions about the management of female PFM.
Keywords: Diagnostic accuracy; Pelvic floor; Women's health; CIENCIAS DA SAUDE::FARMACIA